1979
DOI: 10.1038/281677a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of platelet aggregation by native and desialised alpha-1 acid glycoprotein

Abstract: The alpha-1 acid glycoprotein (orosomucoid; AAG) is a normal constituent of human plasma (650+/-215 microgram ml(-1)) which increases in concentration as much as fivefold in associations with acute inflammation and cancer, and thus is recognized as an acute phase protein. AAG consists of a single polypeptide chain, has a molecular weight of 44,100, and contains approximately 45% carbohydrate including 12% sialic acid; it is the most negatively charged of the plasma proteins. Certain of the biological propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 9 publications
3
50
1
2
Order By: Relevance
“…During acute inflammation, ␣-1 acid glycoprotein also inhibits platelet aggregation by thrombin, collagen, and ADP, acting on the second wave of aggregation. Removal of sialic acid from ␣-1 glycoprotein decreases its inhibitory effect (34). On the other hand, desialylation of plasminogen with a sialidase specific for ␣233-linkages, promotes fibrin proteolysis without the requirement of tissue plasminogen activator (35).…”
Section: Resultsmentioning
confidence: 99%
“…During acute inflammation, ␣-1 acid glycoprotein also inhibits platelet aggregation by thrombin, collagen, and ADP, acting on the second wave of aggregation. Removal of sialic acid from ␣-1 glycoprotein decreases its inhibitory effect (34). On the other hand, desialylation of plasminogen with a sialidase specific for ␣233-linkages, promotes fibrin proteolysis without the requirement of tissue plasminogen activator (35).…”
Section: Resultsmentioning
confidence: 99%
“…It is a positive APP ; after induction by turpentine injection, AGP becomes one of the dominant proteins expressed by the liver and is known to accumulate at sites of inflammation. AGP has shown many immunoregulatory properties : the ability to inhibit platelet aggregation [107], an involvement in wound healing (possibly through its interaction with collagen), the inhibition of neutrophil activation, inhibition of phagocytosis, and it possesses non-specific immunosuppressive properties [105,108]. AGP has an unusually high carbohydrate content of 40 % and is consequently unusually acidic and soluble [106] ; several studies show that the deglycosylated protein demonstrates little or none of AGP's immunosuppressive properties.…”
Section: Immune Modulationmentioning
confidence: 99%
“…AGP function is still unknown; however, this protein is suggested to have a complex role by differentially regulating inflammatory responses (Logdberg & Wester, 2000;Fournier et al, 2000). So far, the most important function of AGP is linked to its ability to inhibit platelet aggregation (Snyder & Coodley, 1976;Costello et al, 1979).…”
Section: Alpha1-acid Glycoprotein (Agp)mentioning
confidence: 99%
“…In a model of bacterial septic shock, using the gram-negative Klebsiella pneumoniae, AGP showed clear protection when given prior to the lethal challenge (Fournier et al, 2000). Furthermore, AGP was found to inhibit apoptosis and inflammation in murine models, and to induce cAMP-dependent signaling in the endothelial cells (Libert et al, 1994;Costello et al, 1979). Using Escherichia coli LPS, an initiator of the acute inflammatory response associated with septic shock, Morre DF and coworkers (1997) demonstrated that AGP-LPS complexes can activate mouse macrophages in vitro and that AGP protects against sepsis.…”
Section: In Vivomentioning
confidence: 99%